Mantra Musicalization: Cowongan Rituals Ideas for Creating Instruction Karawitan Compositions | Musikalisasi Mantra: Ritual Cowongan sebagai Ide Penciptaan Komposisi Karawitan - Yofan Dwi Irawan; Anon Suneko; I Ketut Ardana (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
Banyumas has a cowongan that aims to invoke fertility and prosperity to Dewi Sri. Ritual cowongan uses mantras as an absolute requirement in its implementation. However, as the times progressed, the mantra experienced dissection, so it was necessary to revitalize the mantra into a musicalization model in order to maintain the existence of the mantra. This research uses the research method of practice as research through performance which goes through pre-work, working on and post-work stages to get the best data about the works of art that will be created. The performance of a musical composition with the title Sirêng uses the cowongan as inspiration in creating works of art. Based on the results of the analysis on the cowongan , three elements were found, namely subject, object and activity. These three elements are packaged and implemented into the cowongan which is the workflow of Sirêng's composition. The addition of spells is done to complement the existing spells and complete the workflow. Mantras that are usually spoken simply can be transformed into a musicalization of mantras. The musical elements used to transform the mantra are tempo, melody, time, dynamics and harmony. The packaging of spells into musical performances has a plot and is dramatic. Therefore, the spell will be easier to enjoy and can meet today's tastes.